Identification and Characterization of a Multifunctional Biocontrol Agent, Streptomyces griseorubiginosus LJS06, Against Cucumber Anthracnose - Chai, Chien Hao; Hong, Cheng-Fang; Huang, Jenn-Wen (Frontiers in Microbiology, 2022)
Twenty-eight bacterial strains isolated from Chinese herb extracts, beer fermentation waste, and raw oyster shells were evaluated for their efficacy in controlling cucumber anthracnose. Four bacterial strains, namely TG01, TG02, LJS06, and LJS08, were found to effectively reduce the mycelial growth of Colletotrichum orbiculare COC3 on PDA media. Spraying or drenching LJS06 spore suspension before inoculation significantly (p < 0.05) reduced disease severity; thus, LJS06 was subject to further characterization. On the basis of the morphological, physiological, and biochemical characteristics and a multilocus sequence analysis of partial 16S rRNA, atpD, rpoB, and trpB genes, LJS06 was identified to be Streptomyces griseorubiginosus (Ryabova and Preobrazhenskaya) Pridham et al. Physiological and biochemical tests revealed that S. griseorubiginosus LJS06 can produce amylase, cellulase, chitinase, protease, siderophore, polyamines, and indole-3-acetic acid. Thus, a culture filtrate of LJS06 (specifically SL06) was formulated and evaluated for its efficacy against conidial germination, appressorium formation, and anthracnose management. Diluted SL06 was found to significantly (p < 0.05) inhibit conidial germination and appressorium formation, which can be attributed to impaired membrane integrity, accumulated reactive oxygen species, and impaired energy metabolism in the conidia. In addition, the spraying and drenching of diluted SL06 before inoculation consistently and significantly (p < 0.05) reduced anthracnose severity. These results jointly suggest that S. griseorubiginosus LJS06 can aid in the management of cucumber anthracnose by directly inhibiting conidial function and priming the plant defense system.